The civil war generals comrades, peers, rivals--in their own words - Girardi, Robert I. (Zenith Press, 2013)
The Civil War Generals offers an unvarnished and largely unknown window into what military generals wrote and said about each other during the Civil War era. Drawing on more than 170 sources--including the letters, diaries, and memoirs of the general officers of the Union and Confederate armies, as well as their staff officers and other prominent figures--Civil War historian Robert Girardi has compiled a valuable record of who these generals were and how they were perceived by their peers. The quotations within paint revealing pictures of the private subjects at hand and, just as often, the people writing about them--a fascinating look at the many diverse personalities of Civil War leadership. More than just a collection of quotations, The Civil War Generals is also a valuable research tool, moving beyond the best-known figures to provide contemporary character descriptions of more than 400 Civil War generals. The quotes range in nature from praise to indictment, and differing opinions of each individual give a balanced view, making the book both entertaining and informative. A truly one-of-a-kind compilation illustrated with approximately 100 historical photographs, The Civil War Generals will find a home not only with the casual reader and history buff, but also with the serious historian and researcher